Analisis Harga Laptop Dikalangan Mahasiswa - Samahwati Samahwati; Siti Rohayu; Syamsul Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze students' preferences and perceptions regarding laptop prices as essential tools for academic activities. Laptops are a primary necessity for students to support learning activities such as completing assignments, attending online classes, and conducting research. This research uses a quantitative approach with a survey method involving 197 management students at Bina Bangsa University. Data were collected through a questionnaire covering variables such as price, specifications, brand, and purchasing preferences. The analysis shows that the majority of students prefer laptops priced below IDR 7,000,000, prioritizing specifications that enhance work efficiency, such as storage capacity and processor speed. Brand reputation also significantly influences purchasing decisions, as well-known brands are perceived to be more reliable despite their higher prices. This study concludes that affordability, appropriate specifications, and brand reputation are the main factors influencing students' choices in purchasing laptops. The findings provide insights for manufacturers to design products that align with students' needs and purchasing power.